Improving women’s experiences with gestational diabetes from culturally and linguistically diverse backgrounds in Australia: a qualitative study - Lau, Hiu Wing Rachel; Dong, Johnathon; Weir, Tessa; Chopra, Meenakshi; Olivetti, Lyn; Fulcher, Gregory; Glastras, Sarah (Frontiers in Public Health, 2024)
Introduction Gestational diabetes mellitus (GDM) is the fastest growing type of diabetes in many countries worldwide, including Australia. Although studies have explored the experiences of women with GDM from ethnic minority groups, few have compared their experiences with women from Anglosphere backgrounds. Objective To investigate the responses to diagnosis, the management of GDM, and the experiences of healthcare services among women with GDM from different culturally and linguistically diverse (CALD) backgrounds. Methods Participants were recruited via convenience sampling by advertisement posted around antenatal clinics of three hospitals in NSLHD: Royal North Shore, Hornsby, and Manly Hospitals. The interviews were semi-structured, one-on-one, and in-person conducted by a trained female volunteer. The interviews were audio-recorded, transcribed into text. The data was analyzed via an inductive and descriptive coding approach. The codes were then categorized into main themes and sub-themes. Results 30 women (7 Australian-born, 11 Chinese, 8 Indians, and 4 Koreans) partook the semi-structured interviews and 5 themes were identified: (1) Reaction to diagnosis; (2) Management issues; (3) Roles of friends and family; (4) Information access; and (5) Experience with healthcare services. The lack of culturally tailored dietary information, social support and language barriers were the main factors underpinning the differences in GDM experiences among women from CALD backgrounds versus Australian-born. Conclusion Healthcare models should provide more emotional support upon diagnosis, culturally tailored guidelines for lifestyle modifications, and involve friends and family in care and management to enhance the experience of GDM for women from CALD backgrounds.